Penerapan Fintech Sebagai Platform Modal Kerja Bagi Pengrajin Bakul Purun di Banjarbaru - Ali Sadikin; Dahniar Dahniar; Fahmi Roy Dalimunthe; Muhammad Yudi Rachman; Lily Permata Sari (Universitas Lambung Mangkurat, 2022)
Many UKM in Indonesia are experiencing problems in their business. There are also problems faced by UKM including very small business capital, not applying digital marketing to their products until products are monotonous (less attractive). What's more, during the current covid-19 pandemic, sluggish economic conditions, UKM Bakul Purun